Climatological variations in daily hospital admissions for acute coronary syndromes - Panagiotakos, D. B.; Chrysohoou, C.; Pitsavos, C.; Nastos, P.; Anadiotis, A.; Tentolouris, C.; Stefanadis, C.; Toutouzas, P.; Paliatsos, A. (International Journal of Cardiology, 2004)
Objective: We examined the association between climatologic parameters and daily admissions for non-fatal acute coronary syndromes (ACS) to emergency units of hospitals in the greater Athens area, from January 2001 to August 2002. Methods: Daily mean, maximum and minimum temperatures, relative humidity, wind speed, barometric pressure and a thermo-hydrological index (T.H.I.) were measured at the meteorological station of the Laboratory of Climatology of the Geology Department of the University of Athens. In addition, the daily number of admissions for acute myocardial infarction or unstable angina in the five major general hospitals in the greater Athens area was recorded. Generalized additive models (GAM) were applied to regress-time-series of daily numbers of outpatients with acute cardiac events against climatological variations, after controlling for possible confounders and adjustment for over dispersion and serial correlation. Results: Five thousand four hundred fifty-eight Athenians with non-fatal acute cardiac events were admitted to the selected hospitals during the period of the study, 4093 (75%) males and 1365 (25%) females. There was a negative correlation between hospital admissions and mean daily temperature (MDT) with a 1Β°C decrease in mean air temperature yielding a 5% increase in hospital admissions (P<0.05). This association was stronger in females and the elderly (P<0.01). Relative humidity was positively correlated with hospital admissions (P<0.05). Conclusion: Despite the relatively short study period (<2 years), these findings suggest a significant association between cold weather and increased coronary heart disease incidence, especially in the elderly and females. Β© 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: Acute coronary syndromes; acute heart infarction; Adult; Age Factors; Aged; air temperature; Angina, Unstable; article; Climate; Climatologic parameters; controlled study; correlation analysis; Daily admissions; emergency ward; Female; general hospital; Greece; heart muscle ischemia; hospital admission; human; Humans; humidity; hydrology; major clinical study; Male; Meteorology; Middle Aged; Myocardial Infarction; outpatient; Patient Admission; pressure; priority journal; Seasons; Sex Factors; temperature measurement; unstable angina pectoris; velocity; wind